FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN ULANG PUSKESMAS SANTUN LANSIA KARANGDORO KOTA SEMARANG TAHUN 2016 - Setyarini, Reni; Arso, Septo Pawelas; Suparwati, Anneke (Fakultas Kesehatan Masyarakat, 2017)
Mannered elderly program is a development program of the government for health care of elderly who was launched in 2003. One of the health centersÂ who does the program is Karangdoro mannered elderly center. Courtesy visit to the Karangdoro mannered elderly center is still bellow the target of DKK. In 2015, elderly visitors in Karangdoro mannered elderly center less than 50% from the total elderly registered in health center and still fluktuative. The aim of research to analyze the factors - factors related to interest reuse of Karangdoro mannered elderly centers. This type of research is explanatory research study with cross sectional study design. The population is the elderly who have been using services in health centers totaled 1,704 and sampling technique is accidental sampling obtained a sample of 100 respondents. The analysis of the data was employed univariate and bivariate analysis with Chi Square Test. The results showed that the variables associated with reuse in Karangdoro mannered elderly center is counter service (p value 0.001), inspection service (p value 0.001) and service facilities (p value 0.001). Variables that are not associated are knowledge (p value 0.093), the means of financing (p value 0.664), distance (p value 0.878), transportation costs (p value 0.622), and family support (p value 0.075). Suggestion for health centers that are committed to putting the elderly in the service counters, priority to services to the elderly except for emergency patients, and providing a means of friendly elderly.